Run to the hills: phylogeny of the neotropical high-altitude tarantulas Hapalotremus (Araneae: Theraphosidae) - Ferretti, Nelson Edgardo (2023)
The genus Hapalotremus includes 14 species of medium-sized tarantulas distributed in Argentina, Bolivia and Peru and most of its species are found at high altitude environments along the Andes. These spiders inhabits mainly Puna mountainous grasslands and high cloud forests, but they can be observed in extreme environments, where permanent altitude glaciers are common. Because most of the diversity of this genus has been described in the last five years, more species are expected to be discovered in the short time, and thus an hypothesis of the phylogenetic relationships of the species is crucial for future discoveries. The present study is aimed at the cladistics analysis of all known Hapalotremus species including as well a new species from Urcos, Peru and also provides discussions on its relationships with other close related genera. The outgroups included representatives of Catumiri, Bistriopelma, Bumba and Antikuna. Our preliminary results were based on parsimony analyses of a matrix with 21 terminal taxa scored for 69 morphological characters that suggested Hapalotremus as monophyletic, with most of its component species emerging in two main clades. Hapalotremus apasanka was found to be the most basal species among the genus, and H. hananqheswa, H. major and H. kaderkai as sister species of the remaining clades. Hapalotremus sp. nov. was found close to H. vilcanota supported by the white ventral abdomen and apical projections of spermathecae well-developed and laterally projected. From the phylogeny obtained, Antikuna was found to be the sister genus of Hapalotremus supported by four synapomorphies.